Maternal and fetal characteristics associated with successful Vaginal Birth After Cesarean (VBAC) in Dr. Soetomo and Universitas Airlangga Hospitals, Surabaya, Indonesia - Armawa, Syihab; Sulistyono, Agus; Akbar, Muhammad Ilham Aldika; Risa Etika (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS High VBAC success rate demonstrated with effective patient selection and intrapartum management. Cervical dilation >4 cm at admission identified as a critical predictor of VBAC success.   ABSTRACT Objective: This study aims to evaluate the maternal and fetal characteristics associated with successful vaginal birth after cesarean (VBAC) at Dr. Soetomo General Academic Hospital and Universitas Airlangga Hospital in Surabaya, Indonesia. Materials and Methods: A retrospective analytic study was conducted using a total sampling method to review medical records from January 2021 to December 2022. Inclusion criteria encompassed singleton pregnancies with a previous one-time low-segment cesarean section, vertex presentation, and no contraindications to vaginal delivery. A total of 46 eligible cases were analyzed following exclusion criteria. Results: Among the studied variables, cervical dilation at admission and the 5-minute Apgar score were significantly associated with successful VBAC (p < 0.05). All patients presenting with cervical dilation >4 cm delivered vaginally, indicating a strong predictive value. In contrast, those with dilation <4 cm had a markedly higher rate of cesarean delivery. A higher Apgar score also correlated positively with VBAC success, suggesting favorable neonatal outcomes in these cases. Maternal BMI did not show a statistically significant association with VBAC success (p > 0.05), likely influenced by the predominance of obesity in the cohort. Other factors, including maternal age, parity, birth interval, gestational age, and neonatal birth weight, were not significantly associated with the outcome. Conclusion: While most maternal and fetal variables did not significantly impact the likelihood of successful VBAC, cervical dilation on admission emerged as a critical clinical predictor. These findings emphasize the importance of intrapartum evaluation, particularly cervical assessment, in guiding delivery planning for women with prior cesarean sections.